The Impact of Oil Rent, Currency Overvaluation, and Institution Quality, on Economic Growth of Oil-Rich Countries: A Heterogeneous Panel Data Study - Motameni, Alireza (International Journal of Energy Economics and Policy, 2021)
This paper investigates several key challenges faced by oil-rich countries regarding their economic growth and development. First, it discusses how to determine currency overvaluation for these countries (if any). To determine the overvaluation, the real exchange rate (RER) is calculated and the Balassa–Samuelson effect is estimated via a regression model. Next, the study presents an empirical model for assessing the impact of oil rent on economic growth in the context of currency overvaluation and the institutional quality in every country. As a dynamic model, both endogeneity and heterogeneity are expected across cross-sections because countries are different in culture, customs, and political institutions. Consequently, heterogeneous panel data analysis is undertaken using the error correction model cointegration technique and the mean group estimation method in an autoregressive distributed lag model. Finally, the study concludes the findings and provides policy recommendations by offering a new perspective on an ongoing dilemma, discussing the challenges and limitations facing developing oil-rich countries and how their path to success may differ from other countries. Keywords: Natural resources; Rent-Seeking; Institutions; Economic Growth; Energy Economic JEL Classifications: D72; E02; F43; O47; Q43 DOI: https://doi.org/10.32479/ijeep.10971